2011
DOI: 10.1017/s1368980011002096
|View full text |Cite
|
Sign up to set email alerts
|

To what extent do weight gain and eating avidity during infancy predict later adiposity?

Abstract: Objective: To determine the extent to which weight gain and eating behaviours in infancy predict later adiposity. Design: Population-based, prospective, longitudinal birth cohort study. Weights collected in infancy were used to calculate Z-scores for weight gain to age 1 year conditional on birth weight (CWG). To avoid multiple significance tests, variables from the parent questionnaire completed at age 1 year describing eating avidity were combined using general linear modelling to create an infancy avidity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…This apparent paradox reflects the fact that, while there undoubtedly is an association between infant weight and later overweight, it is not clear how important that association really is. Thus, a German study found that while weight change over the first 2 years of life was the best predictor of a body mass index (BMI) in the obese range at school entry, still only one in five children with rapid weight gain went on to have obesity (4) and we made a similar observation in a UK cohort (10).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…This apparent paradox reflects the fact that, while there undoubtedly is an association between infant weight and later overweight, it is not clear how important that association really is. Thus, a German study found that while weight change over the first 2 years of life was the best predictor of a body mass index (BMI) in the obese range at school entry, still only one in five children with rapid weight gain went on to have obesity (4) and we made a similar observation in a UK cohort (10).…”
Section: Introductionsupporting
confidence: 60%
“…Routine weights measured at school entry (age 4–5) were retrieved from routine data records (mean age 4.9). Data were further collected from 585 children at age 6–8 years at school and/or home visits (mean age 7.5) .…”
Section: Methodsmentioning
confidence: 99%
“…This revealed that CWG generally showed a stronger association with measures of height, BMI and lean mass than with adiposity at age 7 years (37) .…”
Section: Infancy Eating Avidity Score As a Predictor Of Growth And Admentioning
confidence: 94%
“…The children were studied prospectively using parent report questionnaire shortly after birth at 6 weeks and at 4, 8, 12 months. The cohort has since been re-traced at school entry, parent report questionnaires completed at 5-8 years, and a range of anthropometric and body composition measures collected at age 7-8 years [8,15].…”
Section: Prediction Children Weight At School Entrymentioning
confidence: 99%